Fluxos de capitais para os países emergentes: A vis\~ao do FMI - Luiz Afonso Simoens da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The IMF has always supported the free financial flows of capital, based on the concept that they improve economic growth in itself. This perception has debilitated since the global economic crisis beginning in 2007. The purpose of this paper is to analyze the evolution of the IMF's way of understanding this issue; weather it were or not an important improvement to guide the future exchange policies of their shareholders. Still, it's relevant to highlight the impacts of these flows on the volatility of the exchange markets, and consequently on the macroeconomic consistence of developing countries.
Keywords: F32; F38; 330; international capital flows; emergent countries; exchange markets volatility